Learner's Boredom in the Araling Panlipunan (Social Studies): Uncovering Its Factors, Teachers' Reactions, and the Pedagogical Innovations through Key Informant Interview - Nuñez - Del Prado, Bernadette; Luto, Rommuel; Pagulayan, Joshua Aaron; Privado-Lacdao, Ma. Cyrene (International Journal of Arts, Sciences and Education, 2025)
Abstract — Filipino students find Araling Panlipunan (AP) boring in basic education. However, studies exploring the factors leading to this situation remained insufficient. In this study, the researchers identify the factors that shape the perception of AP as a boring subject. It also describes the reaction formation of AP teachers and the pedagogical innovations employed by the teacher-participants to address the prevailing factors they encounter. Thirteen (13) public high school teachers and fifteen (15) junior high school students across the Division of Marinduque were identified using purposive sampling. Key informant interviews were conducted to explore the experiences of the participants. Thematic analysis through in-vivo coding was used to analyze the qualitative data. The researchers found out that the class scheduling and teacher-centered teaching methods are the major factors shaping the negative perception about AP. These factors create positive and negative reactions among AP teachers. Nevertheless, pedagogical innovations were practiced by the participants to address the identified factors (i.e., ICT integration, multidisciplinary and interdisciplinary approaches). The study concludes that strategizing the instruction properly is very important in teaching secondary Araling Panlipunan to motivate the learners and ease the perceived boredom in taking the subject. Keywords— Araling Panlipunan, high school, pedagogy, phenomenological study, qualitative, teacher education,